MAJAS SARKASME DALAM PENULISAN KOMENTAR PADA “WARTAWAN SENIOR BONGKAR KEBUSUKAN ANTASARI, NASRUDIN DAN PERMAINAN JAHAT PDIP” - NFN Marnetti (SUAR BETANG, 2017)
EdyA Effendi is a senior journalist who wrote comment about AntasariAzhar, Nasrudin and PDIP’s engage in some evils. Antasari Azhar is a former head of Corruption Fight Commission  who was arrested and sentenced for 18 years punishment. The ex of KPK has been free from prison in debating program of couple of candidate of Jakarta Province Governor election on January 2, 2017. Antasari’s chatter got responses from social media users. Many of the written comments about AntasariAzhar are negative. This article aims at describing the form of figurative and language registers language register that used in expressing sarcasm metaphor in the comments of article “Wartawan Senior Bongkar Kebusukan Antasari, Nasrudin dan Permainan Jahat PDIP (Senior Journalist Reveals Antasari’s Evil, Nasrudin And PDIP’s Engage In Some Evils)” (www.idnusa.com).This study was carried out from January to April 2017. The method used is qualitative descriptive method.The data was analyzed by using discourse analysis technique.The result of the study shows that sarcasm metaphor that used in article to be data in the form of words and phrase. The type of words that used is adjectives, nouns and verbs. Besides, the language register used is based on the meaning and the language used. Language register based on meaning can be differed to be metaphor such as hoping, cursing, appealing and expressing. The language registers used are regional languages and foreign languages